Transnational adoptees in healthcare: barriers, resources, and needs - Mattias Strand; Mattias Strand; Natte Hillerberg (Frontiers in Public Health, 2024)
BackgroundAfter decades of research output, it is well established that transnational adoptees—i.e., individuals who are placed for adoption outside their country of birth—exhibit an increased risk of various negative mental health outcomes. Even so, there is a lack of suggestions for preventive measures or treatment interventions targeting the transnational adoptee population in the literature.ObjectiveTo explore experiences, opinions, and needs among adult transnational adoptees in Sweden concerning healthcare in general and mental healthcare in particular.MethodsSixty-six adult transnational adoptees residing in Sweden, born in 15 different non-European countries, were recruited for individual in-depth interviews about their experiences and opinions regarding psychosocial support and healthcare. The interview data were analyzed employing a codebook thematic analysis approach.ResultsThree overarching themes were identified: (a) barriers to adequate treatment, (b) helpful resources in dealing with health-related issues, and (c) health-related needs and suggestions for the development of adequate support. Identified barriers include a lack of insight into and interest in adoptee health, colorblindness and unwillingness to address racism, expectations of gratitude, steep financial costs, lack of support from adoptive parents, and mistrust of support structures that involve adoptive parents or adoption organizations. Participants also describe helpful resources, such as the community of fellow transnational adoptees. Health-related needs and suggestions include more well-defined and easily accessible structures of support, improved knowledge and competence, a broader psychotherapeutic repertoire that better addresses adoption-related themes, improved support in situations that can be particularly stressful for adoptees (such as during pregnancy and as new parents), routine follow-up during childhood and adolescence, and education targeting adoptive parents. The need for greater attention to the well-being of children of transnational adoptees is also highlighted.ImplicationsBased on these findings, a number of recommendations can be made. For example, knowledge about adoptee health should be strengthened, and psychotherapeutic competence in addressing issues related to racism should become a priority. After over 20 years of discussion, one or more national research and knowledge hubs on transnational adoption should be created. Moreover, economic resources should be made available to support transnational adoptees in accessing adequate treatment.